Is carbonyl index a quantitative probe to monitor polypropylene photodegradation?. (June 2016) - Rouillon, C.; Bussiere, P.-O.; Desnoux, E.; Collin, S.; Vial, C.; Therias, S.; Gardette, J.-L.
Abstract: For several decades, authors relied upon the carbonyl index to monitor the photo-oxidation of polypropylene and to account for the degradation of the mechanical properties. This paper starts from one question: is the carbonyl band at 1712 cm −1 in infrared spectroscopy really appropriate to quantitatively measure the extent of oxidation of polypropylene? This article brings a negative answer to this question, and the results given in this paper suggest that carbonyl detection by infrared spectroscopy, despite it has been used for years, is not the absolute probe to monitor the photooxidation of polypropylene. Hence, the article aims to provide new relevant and quantitative criteria. These criteria allow the photo-oxidation of PP to be correlated with properties degradation, the one of interest in this case being the gloss loss, which reflects the loss of the surface mechanical properties. These criteria give an early warning of the degradation and permit anticipating the loss of polypropylene functional properties. There are various criteria that can be proposed, the methyl band at 1456 cm −1 being the easiest way to measure the oxidation. It is shown that the modifications of the methyl absorbance fit quite well the increase of crystallinity, molecular weight, and it quite-well reflects the micro-hardness, this last parameter being well correlated to the loss of gloss.